Silver-coated silicone stents as an approach to prevent bacterial colonization of central airways after tracheobronchial stenting - López-Lisbona, Rosa; Calatayud, Laura; Gilabert-Porres, Joan; Díez-Ferrer, Marta; Borros, Salvador; Ardanuy, Carmen; Santos, Salud; Rosell, Antoni; Martí, Sara (Frontiers in Microbiology, 2025)
RationaleTracheobronchial stents are used to treat central airway obstruction but frequently develop bacterial colonization that can lead to infection.ObjectivesTo identify the microorganisms responsible for stent colonization and to evaluate the in vitro ability of silver-coated silicone to reduce their growth.MethodsBacterial identification and quantification were performed on bronchial washings obtained prospectively from 30 patients before and at the first follow-up after stent placement. Bacterial viability on silver-coated silicone was determined for six clinical isolates and two collection-type strains by confocal microscopy and counts of bacterial colony-forming units.Measurement and main resultsThe most frequently recovered pathogens were Pseudomonas aeruginosa (30%) and Staphylococcus aureus (23%). An increase in bacterial load of colonizing pathogens was observed at the first follow-up after stenting, with long-term persistence of the same bacterial genotype within those patients. Three P. aeruginosa and three S. aureus clinical isolates were selected to evaluate the effect of silver on bacterial colonization. Silver-coated silicone exhibited high bactericidal activity against all isolates tested, with bacterial death ranging from 88 to 96% for P. aeruginosa and from 77 to 88% for S. aureus.ConclusionSilver-coated silicone significantly reduced the viability of the most common pathogens that colonized tracheobronchial stents and may represent a promising option for preventing stent-related infections.